2022
DOI: 10.3389/fped.2022.886551
|View full text |Cite
|
Sign up to set email alerts
|

Management of Children With Food-Induced Anaphylaxis: A Cross-Sectional Survey of Parental Knowledge, Attitude, and Practices

Abstract: BackgroundAnaphylaxis is a life-threatening event, but it is frequently undertreated in pediatric patients with food allergies. Previous studies showed that auto-injectable adrenaline (AAI) is underused by patients and parents. This is especially troubling since fatal anaphylaxis has been associated with delayed adrenaline administration.ObjectivesThis study aimed to investigate parental practice and knowledge in anaphylaxis management, and perceived barriers and facilitators in using AAI.ResultsA retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
2
0
2
Order By: Relevance
“…This was even the case for the six participants who correctly performed the procedure, and for those respondents who had attended AAI training. Our findings agree with other studies that have found that even with training, parents and caregivers have low levels of confidence and high levels of anxiety in correctly using an AAI [ 19 21 ]. This lack of confidence may lead to AAI use hesitancy in which treatment is delayed because caregivers are afraid to use the device.…”
Section: Discussionsupporting
confidence: 92%
“…This was even the case for the six participants who correctly performed the procedure, and for those respondents who had attended AAI training. Our findings agree with other studies that have found that even with training, parents and caregivers have low levels of confidence and high levels of anxiety in correctly using an AAI [ 19 21 ]. This lack of confidence may lead to AAI use hesitancy in which treatment is delayed because caregivers are afraid to use the device.…”
Section: Discussionsupporting
confidence: 92%
“…Mindig "egy lépéssel előrébb kell járniuk" annak érdekében, hogy minimalizálják a gyermek allergénnek való kitettségét és a súlyos reakció előfordulásának esélyét [15]. Ugyan a fatális kimenetelű anafilaxiás esemény előfordulásának valószínűsége kicsinek mondható, az észlelt rizikó mégis állandó aggodalmat és félelmet válthat ki az érintettekből a mindennapok során [16,17]. Súlyos allergia esetén a szülők gyakran felülbecsülik a halálos kimenetelű allergiás reakciók előfordulásának valószínűségét [12].…”
Section: Súlyos Gyermekkori éTelallergiával Való Együttélés a Családbanunclassified
“…Ugyanakkor az adrenalin-autoinjektorok használata mégis alulmarad a tényleges anafilaxiás reakciók számához képest, ami az autoinjektorok alkalmazását övező kétségekkel magyarázható (például: mikor kell beadni az EpiPent?) [16].…”
Section: Súlyos Gyermekkori éTelallergiával Való Együttélés a Családbanunclassified
“…3 In the case of pediatric patients, caregivers typically bear the responsibility of recognizing anaphylaxis symptoms, carrying, and administrating AAI to the child when required. 4 There are no published data on the optimal age to transfer responsibilities for recognition and treatment of anaphylaxis from caregiver to child. The European Academy of Allergy and Clinical Immunology (EAACI) recommends preparing children for the transition of anaphylaxis responsibility from early adolescence, that is 11-13 years.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal management of anaphylaxis involves avoiding known triggers, use of adrenaline auto‐injectors (AAI) when necessary and devising a personalized anaphylaxis management plan 3 . In the case of pediatric patients, caregivers typically bear the responsibility of recognizing anaphylaxis symptoms, carrying, and administrating AAI to the child when required 4 …”
Section: Introductionmentioning
confidence: 99%